Por trás do não aprender: um olhar psicanalítico - Rennó, Eliane Teixeira (2018)
Starting from the hypotheses that, from an early age, the individual may have difficulties in relation to the stages of learning, impediments to becoming sufficient in their school learning and presenting difficulties in their academic and/or professional development, this research verified what lies beneath non-learning under a psychoanalytic view. The theoretical-methodological approach used is that of listening research and investigation research (NAFFAH NETO; CINTRA, 2012). Three clinical cases, transcribed with reports and vignettes, and collected from unidentified collaborators served as a basis for seeking answers to the following research questions: Which factors in the initial bond prevent a person form interacting with knowing/learning? What causes a person not to relate well to the pursuit of knowledge? What would the reason for them not to develop in the academic and professional spheres be? The concepts that underlie this study are mainly those of intellectual inhibition (KLEIN, 1931) and those on the primitive aspects of development and also those present in A theory of thinking (BION, 1962c), presenting the concepts of alpha function, reverie, K and (-K) link and learning from experience. In conclusion, this research revealed that learning/knowing difficulties are related to how the baby‘s early experiences in parental bonding occur and that emotional factors significantly influence the way a person interacts whit his/her intellectual development